Integrasi Six Sigma (DMAIC) dan Metode Taguchi untuk Optimasi Parameter Proses dan Reduksi Defect pada Produksi Aluminium Foil - Zulkani Sinaga; Achmad Muhazir; Dede Rukmayadi; Afgan Sandy Putra (Universitas Teuku Umar, 2026)
The high defect rate in aluminium foil production can reduce production efficiency and product quality. This study aims to analyze the main causes of defects and determine optimal process parameters to improve aluminium foil production quality. The research applies the Six Sigma approach through the DMAIC (Define, Measure, Analyze, Improve, Control) framework combined with the Taguchi method for process parameter optimization. In the measurement stage, the process capability analysis shows a Defects per Million Opportunities (DPMO) value of 85,084 with a sigma level of 3.116, indicating that the process performance is still at a moderate capability level. Root cause analysis using fishbone diagrams and Failure Mode and Effect Analysis (FMEA) identifies temperature and machine speed as the dominant factors affecting defect occurrence. Furthermore, Taguchi experimental design using an L9 orthogonal array is applied to determine the optimal parameter combination. The results show that the optimal parameters are a temperature of 154 °C and a machine speed of 250.208 m/min. The implementation of these parameters reduces defect levels, where the DPMO decreases to approximately 55,304 and the sigma level increases to about 3.35, indicating an improvement in process capability and stability. This improvement is also supported by the control chart results, which show that the process is within statistical control limits after improvement. Therefore, the integration of Six Sigma and Taguchi methods is proven effective in reducing defects, improving process capability, and enhancing the overall quality of aluminium foil production.